IMPACT OF SOCIAL MEDIA ON MENTAL HEALTH: A COMPREHENSIVE REVIEW OF ADOLESCENT WELL-BEING - Prof. Valentina Rossi (Modern American Journals, 2025)
The pervasive use of social media among adolescents has raised concerns regarding its impact on mental health. While social media platforms offer opportunities for social connection and self-expression, they have also been linked to various mental health challenges, including anxiety, depression, body image issues, and loneliness. This paper provides a comprehensive review of the literature on the relationship between social media usage and adolescent mental health. A significant body of evidence indicates that excessive or negative social media engagement can exacerbate mental health issues, especially in vulnerable adolescent populations. The review explores the mechanisms through which social media influences well-being, such as social comparison, cyberbullying, and sleep disruption. Additionally, the role of social media in fostering social support and resilience is also discussed. Finally, recommendations for mitigating the adverse effects of social media on adolescent mental health are proposed, including increased media literacy, parental involvement, and platform regulation.
Keywords: Social media, adolescent well-being, mental health, depression, anxiety, body image, cyberbullying, social comparison, media literacy, adolescent development.